Effect of thermal annealing on kaolin from the Amazon region, aiming at the production of geopolymer - Maruoka, Luz M.A. [UNESP]; Pinheiro, Isnailson F.; Freitas, Hilderson S.; Nobre, Francisco X.; Scalvi, Luis V.A. [UNESP] (Elsevier, 2023)
In the focus of environmental problems and climate change, research for alternative materials becomes essential. In this sense, research on geopolymers is very relevant, due to its sustainability characteristics linked to mechanical and physical properties. Metakaolin is a geopolymer precursor and obtained from kaolin, whose characteristics, which are specific to each region, impact on the characteristics of metakaolinite, which in turn influences the production of geopolymer. Characteristics of metakaolin from the Amazon region are not well known, with few publications, despite the importance of the region in the international context in terms of natural resources and environmental. In order to contribute to this research, the present investigation analyses the effect of thermal annealing temperature on kaolin and verifies the suitability of metakaolin as a precursor of geopolymer products. The kaolin in natura was benefited by wet sieving and thermally treated in the range 600 °C to 800 °C. Samples were characterized by XRD, with phases quantification and amorphous fraction obtained by Rietveld method, XRF, TG/DTG, specific surface area, laser granulometry, FTIR, SEM and EDS. An average specific surface area of 1.32 m2/g was identified for kaolin treated at 700 °C, where the amorphous fraction is 91.6% which has almost reached saturation, varying slightly to 800 °C as thermal annealing temperature. Considering environmental aspects and the energy savings, one may state that samples treated at 700 °C may efficiently be used as geopolymer precursor material. The vibration of the O–H bond in kaolinite treated at temperatures greater than 650 °C was not identified. Results suggest that the metakaolinite obtained from Amazon kaolin is indicated for geopolymer production.
Keywords: Amazon; Geopolymer; Kaolin; Thermal annealing